Quantitative ultrasound parameters of the calcaneus professional soccer players: Influence of preferred versus non-preferred leg - Kamanli, A; Ozgocmen, S; Kutlu, M; Suluhan, O; Ardicoglu, O (Elsevier Science Inc, 2003)
[Abstract Not Available]
1ST Joint meeting of the International-Bone-and-Mineral-Society/Japanese-Society-for-Bone-and-Mineral-Research -- JUN 03-07, 2003 -- OSAKA, JAPAN